The relevance of recognizing clinical and morphologic features of pityriasis lichenoides: clinicopathological study of 29 cases - Jandrei Rogério Markus (Mattioli1885, 2013)
Background: Pityriasis lichenoides (PL) is a lymphoproliferative disease of unknown origin; its diagnosis is based on clinical characteristics and confirmed by histology.